Role of different orthopedic biomaterials on wear of hip joint prosthesis: A review. (2018) - Chethan, K.N.; Satish Shenoy, B.; Shyamasunder Bhat, N.
Abstract: The wear of the bearing surfaces of hip joint prostheses is a key problem causing their primary failure. Hard-on-soft bearings have suffered long term failure due to polyethylene wear debris induced Osteolysis. This is dependent on the wear volumes and size and shape of the wear debris produced. Small submicron polyethylene wear particles elicit more powerful biological activities than larger particles. This detailed study of wear analysis of hip joint is carried out by highlighting anatomy of hip joint, different materials used in prosthesis, wear and artificial implants such as hard on hard and hard on soft implants for hip joint. It aims to obtain in depth understanding of wear of bearing couples of artificial hip joint due to different parameters.